2014
DOI: 10.3390/ijerph110808058
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with No Dental Treatment in Preschoolers with Toothache: A Cross-Sectional Study in Outpatient Public Emergency Services

Abstract: Many parents rely on emergency services to deal with their children’s dental problems, mostly pain and infection associated with dental caries. This cross-sectional study analyzed the factors associated with not doing an oral procedure in preschoolers with toothache attending public dental emergency services. Data were obtained from the clinical files of preschoolers treated at all nine dental emergency centers in Goiania, Brazil, in 2011. Data were children’s age and sex, involved teeth, oral procedures, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
3
12
0
6
Order By: Relevance
“…Another study, carried out in the PEDS of the same municipality where the present study was conducted, also demonstrated the restriction of dental emergency care in children only to prescriptions, without any effective clinical intervention [8]. It is emphasized that the professional who attends these services must be able to treat dental odontalgias, abscesses, dental trauma, haemorrhages and alveolitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, carried out in the PEDS of the same municipality where the present study was conducted, also demonstrated the restriction of dental emergency care in children only to prescriptions, without any effective clinical intervention [8]. It is emphasized that the professional who attends these services must be able to treat dental odontalgias, abscesses, dental trauma, haemorrhages and alveolitis.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for coping with conditions that require immediate attention in the Unified Health System (SUS) include the Emergency Public Dental Services (PEDS) [5][6][7][8][9][10]. These types of services provide prompt care to dental emergencies, representing an important part of the oral health services system, which is especially reachable to low level social vulnerable people who can't access regular dental treatment [5,6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to the ones obtained in the present study, which indicated that several children and adolescents had received emergency care during their last dental appointment. This could be associated with unequal access to regular dentists [21][22][23], since the main problem related to toothache [8,[24][25][26][27] and to the use of emergency services [11,28,29], the so-called dental caries, is a disease that can be easily prevented and treated when it is diagnosed early on during primary health care. Another important aspect concerns the type of intervention made at UPAs, as such interventions are predominantly palliative [11] and decayed teeth are left untreated, which could quickly lead to a new acute or infectious event.…”
Section: Discussionmentioning
confidence: 99%
“…This fact should be carefully analyzed, especially among preschool children, because when they receive care at an UPA they might not be submitted to procedures that relieve their pain right away [11], allowing pain to persist and interfere with daily activities such as playing, eating, sleeping, and going to school [6,8,9]. Children whose last dental appointment occurred more than 1 year before should be monitored by primary oral healthcare team, thus reducing their use of UPAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation